PENGARUH POLA ASUH ORANG TUA TERHADAP KEDISIPLINAN BELAJAR PESERTA DIDIK - Setiawati, Ai Tia; Hidayat, Yayat (THORIQOTUNA: Jurnal Pendidikan Islam, 2020)
Parent's attention to children is still lacking, caused by several things including busyness, low educational background, lack of parent's direction of everything that has been achieved by the child, causing the child to become indifferent to learning. The problems that arise are how the influence of parenting parents on student learning discipline at MTs Al Hidayah Ciomas Panjalu.This study aims to determine the extent of the influence of parenting on student learning discipline in MTs Al Hidayah Ciomas Panjalu.The method used in this research is descriptive method with quantitative approach. The study population at MTs Al Hidayah was 162 students with a sample of 35 people. Sampling was done by purposive sampling technique. The data collection tool taken was observation and questionnaire as many as 35 respondents, after the data was collected with complete stages. The next step was data analysis using spermant rank coefficient (rs). Parental parenting values in Al Hidayah MTs were obtained at 39.4 at intervals of 38.2 - 40.3 with a fairly good classification. While the learning discipline value of students in Al Hidayah MTs was obtained at 37.97 at intervals of 35.22 - 38.44 with poor classification. Based on the testing of hypotheses that have been done, the results have a pretty good effect between parenting parents with student learning discipline in MTs Al Hidayah. This is obtained from rs = 0.59 with the Guilford scale at an interval of 0.41 - 0.60 with a fairly good classification. The pattern of Oreangtua Parenting affects the Discipline of Student Learning is 35% so 65% is influenced by other factors. The influence of these two variables, namely Parenting Parents Against Student Learning Discipline is a significant correlation. This is evidenced by t_count = 4.20> t_table = 1.69236 so that Ha is accepted and Ho is rejected. Thus Parenting Parents have a pretty good effect on Student Learning Discipline.